Common data elements for radiological imaging of patients with subarachnoid hemorrhage: proposal of a multidisciplinary research group - Hackenberg, Katharina; Etminan, Nima; Wintermark, Max; Meyers, Philip M.; Lanzino, Giuseppe; Rüfenacht, Daniel; Krings, Timo; Huston, John; Rinkel, Gabriel; Derdeyn, Colin (Neurocritical care, 2019)
IntroductionLack of homogeneous definitions for imaging data and consensus on their relevance in the setting of subarachnoid hemorrhage and unruptured intracranial aneurysms lead to a difficulty of data pooling and lack of robust data. The aim of the National Institute of Health/National Institute of Neurological Disorders and Stroke, Unruptured Intracranial Aneurysm (UIA) and Subarachnoid Hemorrhage (SAH) Common Data Elements (CDE) Project was to standardize data elements to ultimately facilitate data pooling and establish a more robust data quality in future neurovascular research on UIA and SAH.MethodsFor the subcommittee ‘Radiological imaging of SAH,’ international cerebrovascular specialists with imaging expertise in the setting of SAH were selected by the steering committee. CDEs were developed after reviewing the literature on neuroradiology and already existing CDEs for other neurological diseases. For prioritization, the CDEs were classified into ‘Core,’ ‘Supplemental—Highly Recommended,’ ‘Supplemental’ and ‘Exploratory.’ResultsThe subcommittee compiled 136 CDEs, 100 out of which were derived from previously established CDEs on ischemic stroke and 36 were newly created. The CDEs were assigned to four main categories (several CDEs were assigned to more than one category): ‘Parenchymal imaging’ with 42 CDEs, ‘Angiography’ with 49 CDEs, ‘Perfusion imaging’ with 20 CDEs, and ‘Transcranial doppler’ with 55 CDEs. The CDEs were classified into core, supplemental highly recommended, supplemental and exploratory elements. The core CDEs were imaging modality, imaging modality type, imaging modality vessel, angiography type, vessel angiography arterial anatomic site and imaging vessel angiography arterial result.ConclusionsThe CDEs were established based on the current literature and consensus across cerebrovascular specialists. The use of these CDEs will facilitate standardization and aggregation of imaging data in the setting of SAH. However, the CDEs may require reevaluation and periodic adjustment based on current research and improved imaging quality and novel modalities.
Gesehen am 27.09.2019